Performance Studies of New Apple Cultivars on Different Rootstock under High- Density Plantation in Cold Dry Temperate Region of Kinnaur, Himachal Pradesh - Kumar, Arun (International Journal of Bio-resource and Stress Management, 2020)
Field experiments undertaken at the Vegetable Research Station, Kalpa farm, Dr YS Parmar University of Horticulture & Forestry, Nauni, Solan H.P., India during the year 2018-19 to study the performance of newly introduced apple cultivation on various rootstock under high-density plantations in the cold temperate region of Kinnaur. The high-density plantation of apples in Kinnaur district is indeed an important aspect in the upliftment of the socio- economic status of farmers in the farming community, keeping in mind that this trial was carried out to benefit the farming community in the coming years. The experiment evaluates four apple cultivars ‘Red Cap Valtod/MM 106’, ‘Red Velox/M9’, ‘Jeromine/M9’ and ‘Super Chief/MM 106’, planted at a spacing of 2.5X1.0 meters. Maximum, shoot extension growth (17.61 cm), trunk Diameter (43.08 mm), plant height (313.13 cm), plant spread (E-W 183.13 cm; N-S (180.75 cm), fruit diameter (81.21 mm), number of fruits per tree (64.25), fruit weight (225.20 kg tree-1), yield (3.58 kg tree) and productivity (14.32 mt ha-1) were recorded with Red Velox on M9, whereas, maximum of flowers number (867.14 tree-1) and fruits tree-1 (20) was seen in Super Chief on MM 106. Higher percent fruit set (23.66%) was recorded with the cultivar Red Cap Valtod on MM 106 and Fruits length (76.20 mm) recorded maximum in cultivar Jeromine on M9. Studies have shown that grafted ‘Red Velox’ plants on M9 is superior in terms of growth, precedence, quality of fruit and productivity and thus it may be recommended to grow under high density plantations in cold temperate conditions of Kinnaur, Himachal Pradesh.